Finite element analysis and experimental verification of press-fit peg push-in and pull-out in trabecular bone analogue - Xiaoyi Min; David Heath; Azmi Rahman; Laurence Marks; David Murray; Stephen Mellon (Results in Engineering)
Aims: Primary fixation of cementless implants is achieved through press-fit. This study aimed to simulate the press-fit of pegs in bone analogue with finite element analysis (FEA) with as few parameters as possible, thereby providing a useful tool for the quick evaluation of potential device designs. Methods: Push-in and pull-out of smooth and porous pegs in plastic trabecular bone analogue (20 PCF, Sawbones) were modelled using a finite element approach. The model was validated by comparing the maximum push-in and pull-out forces from FEA to the corresponding peg push-in/pull-out testing in plastic bone. Results: The results from FEA agreed well with experiments for the smooth pegs at surgically-relevant interferences (0.6–0.9 mm). Error was under 18.4 % for maximum push-in forces and 6.9 % for maximum pull-out forces. When the same fracture strain value was used to simulate porous pegs, the errors were 9.4 % and 14.7 % for push-in and pull-out force, respectively. Conclusion: The proposed method of simulating peg press-fit required only two sets of input data: the uniaxial material curve of the plastic bone from which the fracture strain could also be derived, and the coefficient of friction between the plastic bone and the peg. The method can be applied to gain insight into the potential of new fixation component designs before progression to experimental testing.